Genetic counseling to a DMD asymptomatic carrier: First case report in the Peruvian public healthcare system - Bazalar-Montoya, Jeny (2021)
Duchenne muscular dystrophy (DMD) is a rapidly progressive dystrophinopathy with X-linked inheritance. This report describes a woman with a family history of male relatives affected by DMD, as she sought out genetic counseling about her concerns related to family planning and risks of eventually having children with the disease. We proposed her to get involved in a pilot program for carrier-status diagnosis and genetic counseling. This case illustrates the importance of a genetic counseling program for diagnosis of asymptomatic carriers in neurogenetic diseases, particularly in regions with low-resource settings. We discussed successes and misunderstandings faced throughout the process, supporting policies for present and future challenges from this and similar kinds of diagnoses.